Digital Fashion Communication n (Inter)cultural Perspective - Noris, Alice (Brill, 2022)
Fashion is an integral part of popular culture, closely intertwined with tales, magazines, photography, cinema, television, music and sports...up to the emergence of dedicated exhibitions and museums. Fashion is undergoing a major digital transformation: garments and apparels are presented and sold online, and fashion trends and styles are launched, discussed and negotiated mainly in the digital arena. While going well beyond national and linguistic borders, digital fashion communication requires further cultural sensitivity: otherwise, it might ignite inter-cultural misunderstandings and communication crises. This book presents the recent transformation of fashion from being a Cinderella to becoming a major cultural attractor and academic research subject, as well as the implications of its digital transformation. Through several cases, it documents intercultural communication crises and provides strategies to interpret and prevent them.